2017
DOI: 10.13057/nusbiosci/n090312
|View full text |Cite
|
Sign up to set email alerts
|

Kidney histology in streptozotocin-induced diabetic male Wistar rats treated with combined extract of temulawak rhizome and belimbing wuluh fruit

Abstract: Alipin K, Sari EP, Madihah, Setiawati T, Ratningsih N, Malini DM. 2017. Kidney histology in streptozotocin-induced diabetic male Wistar rats treated with combined extract of temulawak rhizome and belimbing wuluh fruit. Nusantara Bioscience 9: 312-317. Complications that are occurred in patients with Diabetes Mellitus usually followed by kidney damage. Temulawak (Curcuma xanthorrhiza Roxb.) and belimbing wuluh (Averrhoa bilimbi L.) were traditionally used to decrease blood glucose level. Thus, they were potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…The histopathological examination result in this study agrees with Zafar, et al [35] and Alipin, et al [36] who found that the relative kidney weight in STZinduced rat for 12 weeks was significantly higher than that of the non-induced rat. In this study, the Bowman's space in kidneys of diabetic rats was wider than of nondiabetic rats.…”
Section: Discussionsupporting
confidence: 91%
“…The histopathological examination result in this study agrees with Zafar, et al [35] and Alipin, et al [36] who found that the relative kidney weight in STZinduced rat for 12 weeks was significantly higher than that of the non-induced rat. In this study, the Bowman's space in kidneys of diabetic rats was wider than of nondiabetic rats.…”
Section: Discussionsupporting
confidence: 91%
“…ROS stimulate the overexpression of pro-sclerotic growth factors such as tumor growth factor β (TGFβ) and connective tissue growth factor (CTGF). In line with our finding, the percentage of necrosis on the proximal tubule of DM rats was higher than nondiabetes rats [25]. Damage on tubules characterizes pyknosis, karyolysis, and necrosis on the brush border.…”
Section: Comparison Of Age and Rage Expression On Rats Given With Blasupporting
confidence: 91%
“…To further investigate the protective effects of watermelon leaf extract against diabetes, we examined the liver and kidney structures of the experimental animals. These organs are primarily involved in glucose metabolism (Alipin et al, 2017). The kidneys of the diabetic rats showed renal tubular necrosis and hyaline cast formation in the necrotic regions (Chowdhury et al, 2019).…”
Section: Discussionmentioning
confidence: 99%